Soybean defense induction to Spodoptera cosmioides herbivory is dependent on plant genotype and leaf position - de Freitas, Marcelo Mueller [UNESP]; de Souza, Bruno Henrique Sardinha [UNESP]; Nogueira, Luciano [UNESP]; Di Bello, Mirella Marconato [UNESP]; Boiça Júnior, Arlindo Leal [UNESP] (Springer Nature, 2018)
Plants have evolved a diverse array of defensive mechanisms against biotic and abiotic stresses, which can be either constitutive or inducible. Variation in plant-intrinsic factors such as the genotype and the leaf position coupled with insect herbivory can affect the expression of resistance to insects. We investigated if soybean defense induction triggered by Spodoptera cosmioides herbivory varies in function of the genotype and leaf position. This hypothesis was tested in two bioassays using leaf discs or entire leaflets collected from the upper and lower trifoliates of S. cosmioides-injured and uninjured V3-V4 soybean plants. We used one genotype that was constitutively resistant and one that was constitutively susceptible to S. cosmioides based on previous screening. Third-instar larvae were fed one of the treatments and assayed for leaf consumption, larval growth, and efficiency of conversion of ingested food. Genotype and leaf position significantly interacted with herbivory and affected soybean-induced resistance to S. cosmioides. Negative responses on S. cosmioides larvae consumption and growth rates were only observed when leaf material was originated from the upper soybean trifoliate. The susceptible soybean genotype did not exhibit induced resistance characteristics. Food offered as leaf disc was better at demonstrating induced resistance in previously injured soybean, whereas offering entire leaflet the induced effects were less pronounced. Here we provide new findings on soybean resistance by demonstrating that resistance induction to S. cosmioides herbivory is dependent on the plant genotype and leaf position where injury took place, with negative effects better evinced in bioassays using leaf discs than entire leaflets.
Keywords: Black armyworm; Glycine max; Induced resistance; Optimal defense theory; Research methodology